Implementation of Counseling Guidance Services in Overcoming Difficulties of Remindering The Al-Qur'an - Daulay, Nurussakinah; Al Farabi, Mohammad; Ulya, Nurul (KONSELI: Jurnal Bimbingan dan Konseling (E-Journal), 2022)
This study aims to describe the implementation of counseling services to overcome difficulties in memorizing the Qur'an at Madrasah Tsanawiyah Hifdzil Qur'an Islam Center Medan. This research is field research and is qualitative in nature. And also in this study the classification of qualitative descriptive methods. Data collection techniques in this research are observation, interviews, and document studies. Activities in analyzing this data include data reduction, data exposure, and drawing conclusions. The data validity technique adopted is.